Nusinersen demonstrates effectiveness in treating spinal muscular atrophy: findings from a three-year nationwide study in Korea - Cho, Jaeso; Lee, Jiwon; Kim, Jihye; Lee, Hyunjoo; Kim, Min-Jee; Lee, Yun Jeong; Yum, Mi-Sun; Byun, Ji-Hye; Lee, Chong Guk; Lee, Young-Mock; Lee, Jeehun; Chae, Jong-Hee (Frontiers in Neurology, 2023)
Nusinersen is the first drug approved for spinal muscular atrophy (SMA) treatment. In this study, we aimed to evaluate the long-term safety and efficacy of nusinersen, assess the therapeutic effects based on the treatment initiation timing and baseline motor function, and explore the perception of functional improvement from either parents or patients, utilizing 3-year nationwide follow-up data in South Korea.We enrolled patients with SMA who were treated with nusinersen under the National Health Insurance coverage, with complete motor score records available and a minimum treatment duration of 6 months. To evaluate the motor function of patients, the Hammersmith Infant Neurological Examination-2 (HINE-2) was used for type 1 and the Expanded Hammersmith Functional Motor Scale (HFMSE) was used for types 2 and 3 patients. A significant improvement was defined as a HINE-2 score gain ≥ 5 for patients with type 1 and an HFMSE score ≥ 3 for patients with types 2 and 3 SMA. Effects of treatment timing were assessed. Patients with type 2 were further categorized based on baseline motor scores for outcome analysis. We also analyzed a second dataset from five tertiary hospitals with the information on parents/patients-reported impressions of improvement.The study comprised 137 patients, with 21, 103, and 13 patients representing type 1, 2, and 3 SMA, respectively. At the 3-year follow-up, the analysis encompassed 7 patients with type 1, 12 patients with type 2, and none with type 3. Nearly half of all enrolled patients across SMA types (42.8%, 59.2% and 46.2%, respectively) reached the 2-year follow-up for analysis. Patients with type 1 SMA exhibited gradual motor function improvement over 1-, 2-, and 3-year follow-ups (16, 9, and 7 patients, respectively). Patients with type 2 SMA demonstrated improvement over 1-, 2-, and 3year follow-ups (96, 61 and 12 patients, respectively). Early treatment from symptom onset resulted in better outcomes for patients with type 1 and 2 SMA. In the second dataset, 90.7% of 108 patients reported subjective improvement at the 1-year follow-up.Nusinersen treatment for types 1-3 SMA is safe and effective in long-term follow-up. Early treatment initiation was a significant factor affecting long-term motor outcome.